An Examination of the Experiences of Practitioners Delivering Sport Psychology Services within English Premier League Soccer Academies - Francesca Dean; Emma Kavanagh; Amanda Wilding; Tim Rees (MDPI AG, 2022)
Sport psychology has become increasingly recognized and accepted within professional sports, including soccer. To date, there is a lack of research that examines the provision of sport psychology within elite soccer, particularly from the experience of applied practitioners working within the field. The current study adopted a qualitative, inductive approach, to examine the experiences of practitioners responsible for sport psychology delivery within elite soccer academies in England. Seven participants (four females; three males), working within academies in the English Premier League, took part in semi-structured interviews about their experience of delivering sport psychology services within elite soccer academies. Results demonstrated that the provision of sport psychology is continually evolving, yet there are a number of factors that appear to inhibit the full integration of the discipline into academy soccer. Six key themes were identified: The breadth of sport psychology provision; what is sport psychology; the stigma surrounding sport psychology services; psychological literacy; the elite youth soccer environment; and the delivery of sport psychology under the Elite Player Performance Plan. Participants identified a lack of psychological literacy among coaches and academy staff, as well as a low level of guidance regarding the provision of psychology within the England Football Association's guiding document-the Elite Player Performance Plan-leading to considerable variation in the nature of the sport psychology provision. Future research would do well to also sample from a range of staff working within English soccer academies, in order to assess their perception of the level of provision and understanding of psychology.